Hubungan Hukum dan Pertanggungjawaban DSN dengan MUI dalam Operasional Lembaga Keuangan Syariah - Arinta Rachmawati; Ro’fah Setyowati (Perspektif Hukum, 2020)
The rapid development of Islamic economic institutions in Indonesia cannot be separated from DSN and MUI's participation in their operations. This research will specifically discuss the legal relationship and responsibility of DSN with MUI in the process of Islamic Financial Institutions in Indonesia. This research is a normative juridical study using secondary legal data in the form of primary legal materials and secondary legal materials on Islamic financial institutions. Based on the research results, it is known that the legal relationship between DSN and MUI in the operation of Islamic financial institutions, MUI which is the responsible institution for matters related to sharia, places the position of DSN as an extension of the MUI's arm which has a very strategic and central location in terms of the development of the Islamic economy in Indonesia. DSN is responsible for providing supervision and for establishing relationships with DPS and Islamic financial institutions.